2000
DOI: 10.3168/jds.s0022-0302(00)75144-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mechanical Processing on Utilization of Corn Silage by Lactating Dairy Cows

Abstract: We conducted three experiments to determine the influence of mechanical processing on corn silage utilization by lactating dairy cows. Total mixed rations contained either unprocessed or processed corn silage harvested between 1/4 and 3/4 milk line. In trial 1, 12 multiparous Holstein cows were used in a replicated double switchback design with 21-d periods. Intake of dry matter (DM) was increased 1.2 kg/d by processing, but milk yield was unaffected. Processing did not affect apparent total-tract DM digestibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 12 publications
3
33
1
5
Order By: Relevance
“…1) could explain the higher VFA production and lower pH in the rumen of dairy cows fed MPCS (Dhiman et al 2000). A similar trend was observed in incubation with the Rusitec (Table 2), even though ruminal environments were different among these in vitro, in situ and in vivo experiments.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…1) could explain the higher VFA production and lower pH in the rumen of dairy cows fed MPCS (Dhiman et al 2000). A similar trend was observed in incubation with the Rusitec (Table 2), even though ruminal environments were different among these in vitro, in situ and in vivo experiments.…”
Section: Discussionsupporting
confidence: 61%
“…In fact, markedly enhanced VFA with feeding of MPCS was characterized by high acetate (Table 2), which is a representative end-product of cellulolytic bacteria (Ogimoto and Imai 1981). Higher acetate concentration and molar proportion with MPCS feeding, as shown by Johnson et al (2002) and the present Rusitec study, may cause elevation of milk fat production that has been documented in several reports (Dhiman et al 2000;.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…2002a; Cooke & Bernard 2005) in which animals were fed CS harvested at the 3/4 milk line or black‐line stage also reported that MP had no effect on DM intake. However, some studies (Dhiman et al . 2000; Andrae et al .…”
Section: Resultsmentioning
confidence: 99%
“…Many studies reported that MP increased starch digestibility, the amount of total digestible nutrients (TDN), and animal performance (Bal et al . 2000; Dhiman et al . 2000; Johnson et al .…”
Section: Introductionmentioning
confidence: 99%